Criticism and Genealogy of Failure at Different Stages of the Organization's Life Cycle - Manijeh Ghareche; Bahman Hajipour; Akbar Alamtabriz; Masoumeh Mohammadipour Pamsari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Business failure is a very complex process and is influenced by various factors. SME’s are important for every economy but despite their importance, failure and bankruptcy occur among them. The present article presents a more specific approach based on the complementary of theoretical approaches in the field of organization failure and uses three approaches to identify different types of failures in different stages of the organization's life cycle. Criticism and studying the results of systematic review in three stages and trying to link two theoretical foundations of organization life cycle and organization failure studies in order to achieve a better understanding of types of failure in each stage of the life cycle of SMEs by using open and closed Sorting cards to perform data mining, reveals 9 different types of failure. Revealing the types of failures that SME’s may encounter in each stage of their life cycle, compared to the simplistic, single-level view of enterprise failure highlights the appropriate route of policymaking in this area to prevent major damages of these company’s failures.